Ultrafast interface charge separation in carbon nanodot-nanotube hybrids - Sciortino, Alice (2022)
Carbon dots are an emerging family of zero-dimensional nanocarbons behaving as tunable light harvesters and photoactivated charge donors. Coupling them to carbon nanotubes, which are well-known electron acceptors with excellent charge transport capabilities, is very promising for several applications. Here, we first devised a route to achieve the stable electrostatic binding of carbon dots to multi- or single-walled carbon nanotubes, as confirmed by several experimental observations. The photoluminescence of carbon dots is strongly quenched when they contact either semiconductive or conductive nanotubes, indicating a strong electronic coupling to both. Theoretical simulations predict a favorable energy level alignment within these complexes, suggesting a photoinduced electron transfer from dots to nanotubes, which is a process of high functional interest. Femtosecond transient absorption confirms indeed an ultrafast (<100 fs) electron transfer independent of nanotubes being conductive or semiconductive in nature, followed by a much slower back electron transfer (≈60 ps) from the nanotube to the carbon dots. The high degree of charge separation and delocalization achieved in these nanohybrids entails significant photocatalytic properties, as we demonstrate by the reduction of silver ions in solution. The results are very promising in view of using these "all-carbon" nanohybrids as efficient light harvesters for applications in artificial photocatalysis and photosynthesis.